2020
DOI: 10.1186/s12882-020-1702-6
|View full text |Cite
|
Sign up to set email alerts
|

Access to CKD Care in Rural Communities of India: a qualitative study exploring the barriers and potential facilitators

Abstract: Background: Despite the high and rising burden of chronic kidney disease (CKD) in South Asia, factors that influence access to CKD care at the community level have not been studied previously, especially in the rural areas. We conducted a mixed methods study and interviewed key stakeholders to explore the views and experiences of key stakeholders, and identify barriers and potential facilitators that influence access to CKD care at the primary care level in rural India. Methods: A total of 21 stakeholders part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
1
14
0
2
Order By: Relevance
“…23 Problems associated with norms and cultures as well as scarcity of quality healthcare in most rural communities elevated the incidence of this disease in developing countries. 24 To find a lasting solution to neurodegeneration caused by exposure to free radicals and or formation of free radicals in the body system, Ficus platyphylla 80% stem bark was extracted and evaluated for toxicity and anticholinesterase effects on Catfish. Methanol is one of the commonly used solvent for the extraction of plant phytochemical constituents and was reported to be safe compared to the hexane and ethanol.…”
Section: Propionyl-cholinesterase Inhibitory Assaymentioning
confidence: 99%
“…23 Problems associated with norms and cultures as well as scarcity of quality healthcare in most rural communities elevated the incidence of this disease in developing countries. 24 To find a lasting solution to neurodegeneration caused by exposure to free radicals and or formation of free radicals in the body system, Ficus platyphylla 80% stem bark was extracted and evaluated for toxicity and anticholinesterase effects on Catfish. Methanol is one of the commonly used solvent for the extraction of plant phytochemical constituents and was reported to be safe compared to the hexane and ethanol.…”
Section: Propionyl-cholinesterase Inhibitory Assaymentioning
confidence: 99%
“…A recent study in rural India found that a lack of awareness and a shortage of health resources to be barriers to CKD care. 11 Previous studies also suggest that a key difference in CKD management in the West and in Singapore is the centrality of family support. 12 13 One study in Singapore explored the barriers and facilitators to ESKD management (ie, dialysis and kidney transplant) and found that family and peer support enhance self-management, 12 but no other study in Singapore has identified the barriers and facilitators to predialysis CKD management from the patients' perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…2-4 However, some facilitators have been identified in low income settings like India which include improving knowledge & health literacy and access to health services at primary care hospitals. 5,6…”
mentioning
confidence: 99%